Kajian Sosial Budaya dan Ekonomi Dalam tradisi masuk kaum di Muko Muko - hilyati milla mawardi (Puitika, 2020)
The purpose of this study was to determine the procession of Masuk Kaum, the meaning of the symbols that contained in the ceremony and also to view the social activities, cultural and economic community after Masuk Kaum in Muko Muko. The approach of this research was descriptive qualitative which starts from the phenomenological view. The source of the data was primary data that was related to the data of population and the condition of the area of investigation, while the secondary data was related to the data which was obtained from the study from other researcher. Data collection was done by doing observation, interviews, literature study, and documentation. Descriptive qualitative was chosen as the technique of data analysis with steps of descriptive observation, participatory observation, analysis of regional taxonomic analysis and componential analysis. Based on this research it was known that Masuk Kaum was done because of mixed marriages and the use of the customs of Muko Muko which was done by the newcomer. The procession was done in traditional ceremonies. The person who played a role in the process is the head of the tribe. The equipment of procession Masuk Kaum used traditional symbol which were ayam singgang, eggs, nasi kunyit, and water. The social study: there is no difference of social interaction immigrant communities who alredy Masuk Kaum. The economics study: economic activity is not limited to the immigrant communities who already Masuk Kaum. The Cultural Study: Using custom and have rights to a title for newcomer who already Masuk Kaum.